2, 3-Diphosphoglycerate Concentrations in Autologous Salvaged Versus Stored Red Blood Cells and in Surgical Patients After Transfusion. (March 2016) - Scott, Andrew V.; Nagababu, Enika; Johnson, Daniel J.; Kebaish, Khaled M.; Lipsitz, Joshua A.; Dwyer, Ian M.; Zuckerberg, Gabriel S.; Barodka, Viachaslau M.; Berkowitz, Dan E.; Frank, Steven M.
Abstract : BACKGROUND: Stored red blood cells (RBCs) are deficient in 2, 3-diphosphoglycerate (2, 3-DPG), but it is unclear how autologous salvaged blood (ASB) compares with stored blood and how rapidly 2, 3-DPG levels return to normal after transfusion. Therefore, we compared levels of 2, 3-DPG in stored versus ASB RBCs and in patients' blood after transfusion. METHODS: Twenty-four patients undergoing multilevel spine fusion surgery were enrolled. We measured 2, 3-DPG and the oxyhemoglobin dissociation curve (P50 ) in samples taken from the ASB and stored blood bags before transfusion and in blood samples drawn from patients before and after transfusion. RESULTS: The mean storage duration for stored RBCs was 24 ± 8 days. Compared with fresh RBCs, stored RBCs had decreased 2, 3-DPG levels (by approximately 90%; P < 0.0001) and a decreased P50 (by approximately 30%; P < 0.0001). However, ASB RBCs did not exhibit these changes. The mean 2, 3-DPG concentration decreased by approximately 20% ( P < 0.05) in postoperative blood sampled from patients who received 1 to 3 stored RBC units and by approximately 30% ( P < 0.01) in those who received ≥4 stored RBC units. 2, 3-DPG was unchanged in patients who received no stored blood or ASB alone. After surgery, 2, 3-DPG levels recovered gradually over 3 postoperative days in patients who received stored RBCs. CONCLUSIONS: Stored RBCs, but not ASB RBCs, have decreased levels of 2, 3-DPG and a left-shift in the oxyhemoglobin dissociation curve. Postoperatively, 2, 3-DPG levels remain below preoperative baseline levels for up to 3 postoperative days in patients who receive stored RBCs but are unchanged in those who receive only ASB RBCs.